ChemInform Abstract: Preparation, Functionality, and Application of Metal Oxide‐Coated Noble Metal Nanoparticles. Issue 41 (22nd September 2016) - Liu, Shuhua; Regulacio, Michelle D.; Tee, Si Yin; Khin, Yin Win; Teng, Choon Peng; Koh, Leng Duei; Guan, Guijian; Han, Ming‐Yong
Abstract: Review: [67 refs.